PENGARUH ARSITEKTUR KOLONIAL PADA RUMAH ADAT KAMALI BAADIA, KELURAHAN BAADIA, KECAMATAN MURHUM KOTA BAUBAU - siswardin siswardin; ishak kadir; salniwati salniwati (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
The Kamali Baadia traditional house as the last palace of the Buton Sultanate, combines the traditional architectural concepts of Buton and Colonial architects, for this purpose the research aims to find out the architectural form, explain the colonial architectural forms that affect the architectural characteristics of the Kamali Baadia traditional house and to determine the significance of the influence of Colonial architecture on the architectural form of the Kamali Baadia traditional house. This type of research is qualitative, primary and secondary data sources, literature studies, observations, interviews and documentation using morphological analysis, technology, style and significance analysis of component changes. The architectural form of the Kamali Baadia traditional house is a stilt house with an L-shaped floor plan arranged two floors facing North. The Kamali Baadia traditional house is divided into three components, namely legs, body and roof. The influence of Dutch colonial architecture on the Kamali Baadia traditional house is the Indische Empire Style architectural style with a floor plan on the first floor, a shield roof, a two-leaf door inside motif and a two-leaf window as well as an internal motif. Significant analysis of the sign by the influence of Dutch colonial architecture Indische Empire Style architecture has not been significant.